Factors that influence employee loyalty among Petronas employees / Nur Farha Abdul Razak and Nur Habibah Mansor - Abdul Razak, Nur Farha; Mansor, Nur Habibah (2015)
The objective of this study is to investigate the relationship between the independent variables (supervisor support, employee training, rewards and recognition, teamwork, and employee satisfaction) towards employee loyalty. This research examines the influence of supervisor support, employee training, rewards and recognition, teamwork, and employee satisfaction on employee loyalty towards PETRONAS. This research was conducted at PETRONAS Company in Kuala Lumpur which includes 155 employees as respondents. The sample was drawn using simple random sampling method. Data were obtained by distribution and collection of the returned questionnaires in which then analyzed using Statistical Package for Social Science Version 20 (SPSS 20). Five (5) hypotheses were proposed in the study and all five hypotheses were accepted. The findings revealed that all independent variables have a positive relationship towards the dependent variables. Thus, several recommendations were suggested for future researches in order to identify the factors affecting employee loyalty among PETRONAS employees.